Deteksi Pergerakan Mata dan Kedipan Untuk Memilih Empat Menu Display Menggunakan Probabilitas Berdasarkan Facial Landmark - Akbar Dicky Purwanto; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Person with disability cannot do the normal daily aktivity. In patients with disabilities, the patient cannot move the whole body and therefore needs to be monitored by a household assistant. However, a household assistant cannot keep monitored for 24 hours continuously. To overcome this problem, this research was created to develop a system that helps people with disabilities to help their daily activities. The system was made to detect the eye movements to select menus from the screen. The menu on the LCD screen contains options including to call the nurse, choose a food menu, and go to the toilet. This system is made using the landmark face method combining with the eye movement detection method. Detection of eye movements will be divided into five, namely looking up, down, left, right and forward. The detection will be implemented in the options menu on the LCD screen so that patients can be helped in their daily lives.